Birth Weight and Length of Stunting Toddlers in Working Area of Seteluk Public Health Center in West Sumbawa in 2019: A Case Study - Ziadatul Munawarah; Pramita Putri Utami; Andy UlmiAprilani; Nurul Hidayati (Alta Dharma Publisher, 2022)
Background: Stunting is a chronic condition that describes stunted growth due to long-term malnutrition. Stunting in toddlers needs special attention because it can hamper children's physical and mental health. Low birth weight and length indicate that the child during the womb experienced a lack of nutritional intake, so the impact on growth was not optimal. Objective: To determine the birth weight and length of stunting toddlers in the working area of Seteluk Public Health Center in West Sumbawa in 2019. Methods: This study used a descriptive research method with a cross-sectional time study conducted in July 2019 in the work area Seteluk Public Health Center, West Sumbawa, West Nusa Tenggara, with a total sample of 97 children under five based on inclusion and exclusion criteria. Results: The birth weight of stunted toddlers showed that of the 97 stunting toddlers, 9 toddlers (9.3%) had abnormal birth weights and 88 toddlers (90.7%) had normal birth weights. Meanwhile, birth length showed that 28 toddlers (28.9%) had abnormal birth lengths, and 69 (71.1%) had normal birth lengths. Conclusion: Birth weight and length are not a risk of stunting, but if a toddler is accompanied by poor nutritional intake and has an infectious disease, the toddler will experience stunting. Recommendation: We hope that all midwifery can provide systematic education routinely on the importance of nutrition in babies to improve the understanding of society and prevent stunting in childhood